2021
DOI: 10.3389/fendo.2021.644927
|View full text |Cite
|
Sign up to set email alerts
|

NP-59 Adrenal Scintigraphy as an Imaging Biomarker to Predict KCNJ5 Mutation in Primary Aldosteronism Patients

Abstract: PurposeSomatic KCNJ5 mutation occurs in half of unilateral primary aldosteronism (PA) and is associated with more severe phenotype. Mutation status can only be identified by tissue sample from adrenalectomy. NP-59 adrenal scintigraphy is a noninvasive functional study for disease activity assessment. This study aimed to evaluate the predictive value of NP-59 adrenal scintigraphy in somatic KCNJ5 mutation among PA patients who received adrenalectomy.MethodsSixty-two PA patients who had NP-59 adrenal scintigraph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A recent examination of 131 I-NP-59 uptake in primary adrenal aldosteronism from adenoma by Lu et al, describe the adrenal-to-liver ratio of 131 I-NP-59 as 2-2.8 following dexamethasone suppression depending on the genetic profile. 43 Similarly, there was a 40 to 75% increased uptake of 131 I-NP-59 in the pathologic adrenal gland versus the normal gland. Consequently, using Lu at al.…”
Section: Discussionmentioning
confidence: 93%
“…A recent examination of 131 I-NP-59 uptake in primary adrenal aldosteronism from adenoma by Lu et al, describe the adrenal-to-liver ratio of 131 I-NP-59 as 2-2.8 following dexamethasone suppression depending on the genetic profile. 43 Similarly, there was a 40 to 75% increased uptake of 131 I-NP-59 in the pathologic adrenal gland versus the normal gland. Consequently, using Lu at al.…”
Section: Discussionmentioning
confidence: 93%
“…The former showed significantly higher tracer uptake (HSUV max , 22.2 vs 10.8; LSUV max , 19.4 vs 9.5; Figure 3) than the latter. We previously reported that patients harboring KCNJ5 mutations had higher NP-59 uptake than wild-type patients 38 . KCNJ5 mutation plays an important role in the pathophysiology of PA and can lead to the persistent overproduction of aldosterone by altered selectivity of encoded potassium channel 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that patients harboring KCNJ5 mutations had higher NP-59 uptake than wild-type patients. 38 KCNJ5 mutation plays an important role in the pathophysiology of PA and can lead to the persistent overproduction of aldosterone by altered selectivity of encoded potassium channel. 39 The mechanism of higher MTO uptake in patients with KCNJ5 mutation is probably because of the overexpression of CYP11B2.…”
mentioning
confidence: 99%
“…NP-59 adrenal scintigraphy is a functional study used to evaluate adrenal cortical activity. Lu et al reported using semiquantitative NP-59 adrenal scintigraphy as an imaging biomarker to predict KCNJ5 mutations in PA patients (133). Among 62 PA patients who underwent NP-59 adrenal scintigraphy with available KCNJ5 mutation status, adrenal-to-liver ratio (ALR) and maximal count ratio between two adrenal glands (contrast, CON) derived from NP-59 adrenal scintigraphy were used to differentiate patients with and without KCNJ5 mutations.…”
Section: Np-59 To Predict Kcnj5 Mutationsmentioning
confidence: 99%